An Imaginative Experience - Wesley M. Mary (London, Black Swan, 1995)
A traveller on an InterCity train returning to London sees a white-faced woman leap from the train and race to the aid of a sheep stranded on its back, unable to rise, in a field. The author draws out a plot of an unforgettable impact: of loss, of release, of a necessarily comic acceptance of fate, of love - the `imaginative experience`.